Analyzing Personal Pronouns in The Sea Beast Movie and Its Application in Teaching Grammar - Purnama, Syahbaniyah; Chasanah, Zulia; Widodo, Sri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The aim of this study is to analyze personal pronouns in The Sea Beast movie and its application in teaching grammar. Personal pronouns, which play a crucial role in sentence construction and clarity, are often misunderstood by students. Using Frank’s (1972) theory, the research categorized personal pronouns into five types: subject pronouns, object pronouns, possessive adjectives, possessive pronouns, and reflexive pronouns. Data were collected from the dialogues in The Sea Beast, and a descriptive qualitative method was employed to analyze and categorize the types of personal pronouns. The results show that subject pronouns were the most frequently used, appeared 378 times, followed by object pronouns 135 times, possessive adjectives 66 times, possessive pronouns 1 time, and reflexive pronouns 2 times. Additionally, the study highlights how these findings can be applied in teaching grammar, particularly in helping students understand the practical use of personal pronouns in context. The movie’s dialogues serve as a rich resource for teaching grammar by providing real-life examples of how pronouns function in conversation. This study demonstrates the value of using movie dialogues in the classroom to enhance students’ understanding of pronouns in grammar context.